Harnessing the sun and wind for economic development?: An economy-wide assessment for Egypt - Al-Riffai, Perrihan; Blohmke, Julian; Breisinger, Clemens; Wiebelt, Manfred (MDPI, 2015)
While the recent political transition in Egypt has delayed much-needed policy reforms, our paper suggests that under certain conditions, fostering the national renewable energy strategy may be a promising way of giving an ailing economy an urgently needed impetus. Based on the literature and results of a renewable-energy focused computable general equilibrium model, we recommend that Egypt supports the generation of wind power. While some energy may be exported to generate foreign exchange, a substantial part of the newly produced energy should be sold domestically to ease existing supply constraints and to avoid Dutch disease effects. In addition, and in order to maximize the benefits of renewable energy sources, the renewable energy strategy should be accompanied by a (further) reduction of energy subsidies. Finally, lessons from other countries suggest that sound institutions; appropriate, clear and lasting regulations; careful technology transfer; and cross-ministerial coordination are important for success.